2022
DOI: 10.21037/atm-22-118
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeted metabonomic analysis of plasma in patients with atherosclerosis by liquid chromatography-mass spectrometry

Abstract: Background: This study sought to analyze non-targeted plasma metabolites in patients with atherosclerosis (AS). Methods:The plasma of patients with AS (the patient group) and the plasma of age-matched and gendermatched healthy individuals (the control group) at the Taihe Hospital was collected. One hundred patients were included in the study (60 in the patient group and 40 in the control group). Fasting venous plasma was collected in the morning. The metabolites in the plasma were examined by liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…The present study confirms the findings of previous studies that suggest that LEA is a relevant NAE implicated in both the metabolic and the inflammatory imbalances associated with obesity [22,25]. While our study on a standard Mediterranean population indicated that plasma concentrations of LEA are associated with obesity and dyslipidemia, the preclinical study regarding diet-induced obesity revealed that the chronic administration of LEA resulted in the normalization of dyslipidemia, an improvement in liver function, and a reduction in inflammatory markers associated with long-term exposure to highfat diets.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study confirms the findings of previous studies that suggest that LEA is a relevant NAE implicated in both the metabolic and the inflammatory imbalances associated with obesity [22,25]. While our study on a standard Mediterranean population indicated that plasma concentrations of LEA are associated with obesity and dyslipidemia, the preclinical study regarding diet-induced obesity revealed that the chronic administration of LEA resulted in the normalization of dyslipidemia, an improvement in liver function, and a reduction in inflammatory markers associated with long-term exposure to highfat diets.…”
Section: Discussionsupporting
confidence: 93%
“…One preclinical study demonstrated that LEA is capable of reducing feeding in rodents and that this effect is abrogated by the pharmacological blockade of Ppar-α receptor, suggesting a similar role for LEA and OEA [24]. In addition, a couple of studies in humans have indicated that its concentration is elevated in obese humans and linked to cardiovascular risk [22,25]. In addition, recent reports have identified LEA as a circulating metabolic biomarker of chronic inflammatory/autoimmune disorders, although its potential contribution to the evolution or prognosis of the disease is unknown [26].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the processes of retinol metabolism with all-trans-13,14-dihydroretinol were significantly increased in the MS group. It has been previously reported that retinol metabolism was closely correlated with MS in adults ( 37 ), and the elevated level of all-trans-13,14-dihydroretinol was also observed in other diseases, including atherosclerosis and cancer ( 38 , 39 ). All-trans-13,14-dihydroretinol was a metabolite of retinol that was produced by retinol saturase (RetSat) ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 90%